2021
DOI: 10.1038/s41388-021-01967-3
|View full text |Cite
|
Sign up to set email alerts
|

KRAS phosphorylation regulates cell polarization and tumorigenic properties in colorectal cancer

Abstract: Oncogenic mutations of KRAS are found in the most aggressive human tumors, including colorectal cancer. It has been suggested that oncogenic KRAS phosphorylation at Ser181 modulates its activity and favors cell transformation. Using non-phosphorylatable (S181A), phosphomimetic (S181D) and phospho/dephosphorylatable (S181) oncogenic KRAS mutants, we analyzed the role of this phosphorylation to the maintenance of tumorigenic properties of colorectal cancer cells. Our data show that the presence of phospho/dephos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…Ionizing [23,24]. After ionizing radiation, multiple pathways (mostly related to the cell cycle) are involved in maintaining genetic integrity [25]. Since the 1960s, scholars have AGING been studying the dependence of radiosensitivity on the pericellular period.…”
Section: Discussionmentioning
confidence: 99%
“…Ionizing [23,24]. After ionizing radiation, multiple pathways (mostly related to the cell cycle) are involved in maintaining genetic integrity [25]. Since the 1960s, scholars have AGING been studying the dependence of radiosensitivity on the pericellular period.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that PRSS2, as an activator of matrix metalloproteinase (MMP), caused the degradation of peripheral collagen by activating interstitial collagenase. serine protease 2 has been proved to be associated with the development of tongue carcinoma, pancreatic carcinoma, colorectal carcinoma and ovarian carcinoma [24][25][26]. The high expression of serine protease 2 in pancreatic carcinoma is related to T phase.…”
Section: Discussionmentioning
confidence: 99%
“…CTNNA1 is highly expressed in DLD-1 cells with phosphor-/ dephosphorylatable K-Ras, a necessary phenotype for maintaining epithelioid morphology and tumor growth, which may be associated with maintaining cell polarization and cell invasion. On the contrary, CTNNA1 expression decreases in cells with phosphomimetic or non-phosphorylatable K-Ras, and cell adhesion decreases accordingly [21].…”
Section: Role Of Ctnna1 In Intestinal Cancermentioning
confidence: 98%